المدلولات القرآنية لقيمة الولاء في سورة العنكبوت - بن عطية, منى; شبايكي, الجمعي (جامعة الوادي university of eloued, 2023)
تتأكّد أهميّة القيم في حياة الأمة الإسلامية اليوم من خلال المرجعيّة التي تستمدّ منها منظومة القيم الكاملة وهي القرآن الكريم وسنّة نبيّه عليه أفضل الصّلاة والتّسليم، ولا يخفى على أحد تراجع فاعليّة القيم في الواقع المعاصر في شتى المجالات، مـمّا أحدث فراغا كبيرا بين الدين والناس ملأته قيم إيديولوجيات غريبة عن الشّريعة الإسلاميّة، من هذا المنطلق جاء هذا البحث إلى تبيان قيمة الولاء في سورة العنكبوت لأجل الوصول إلى الطريقة التي عولجت بها القيمة المدروسة. وقد خلص إلى أهميّة قيمة الولاء كمعيار يحكم السّلوك الإنساني ويوجّهه. The importance of values in the life of the Islamic Nation today is confirmed by the reference from which the entire system of values is derived, namely the Holy Qur’an and the Sunnah of His Prophet, peace and blessings be upon him, and it is no secret to anyone that the effectiveness of the values in contemporary reality is hidden in various fields, creating a great void between religion and people filled with value of ideologies that are alien to the islamic law, so this article come to study the value of loyalty in the light of Surat Al-Ankabut from the purpose of reaching the way in which value was handled, and its importance becomes evident as a criterion rules and builds human behavior
مقال
Keywords: القيم ; سورة العنكبوت ; الولاء ; المدلولات القرآنية